Tinjauan Teoritis Efektivitas Pemeriksaan Pajak Di Indonesia - Setiadi Alim Lim; Lilik Indrawati (BIP's JURNAL BISNIS PERSPEKTIF, 2019)
Each country can use a tax collection system that varies between countries. Basically, each country can choose one of the tax collection systems, namely between the official assessment system or the self assessment system. On the official assessment system the amount of tax payable and must be paid by the taxpayer is determined by the tax authority. Whereas in the self assessment system the amount of tax payable and must be paid will be calculated, deposited and reported by the taxpayer himself. Most countries in the world use the self assessment system. A country that applies the self assessment system will usually experience problems related to the low level of tax compliance. To increase the level of taxpayer compliance, countries that implement the self assessment system must routinely carry out tax audit actions to test the compliance of taxpayers. In order for the purpose of the tax audit to be achieved, the tax audit must be carried out effectively. Indicators that are usually used to assess the effectiveness of tax audits are compliance from taxpayers. The effectiveness of tax audits is also influenced by several factors that can generally be summarized into 7, namely: organization, organizational independence, taxpayer, tax audit quality, tax auditor, regulation, and management support. This research is intended to see whether the tax audit in Indonesia has been running effectively. The effectiveness of tax audits is evaluated by looking at whether the factors that influence the effectiveness of the tax audit have been included in the tax audit in Indonesia. This research is a library research with a statute approach, conceptual approach, and comparative approach. The results of the study show that from the evaluation of all factors that might influence the effectiveness of tax audits, organizational factors, tax auditors, regulations, and management support from the Directorate General of Taxation have met the criteria for the realization of effective tax audits in Indonesia. But the taxpayer factor, the independence of the organization and the tax audit quality have not supported the realization of an effective tax audit. Then when viewed from the level of taxpayer compliance as an indicator that shows that tax audits have been carried out effectively, tax audits in Indonesia have not been effective, because the level of compliance from taxpayers is only at 62.96% for corporate taxpayers and non-individual taxpayers employees and Compliance Ratio Submission of Annual Income Tax Returns in 2017 only reached 72.64%.